A geopolitically aware EU and its Eastern European neighbours: More realism, more investment - Barbara Lippert (Stiftung Wissenschaft und Politik (SWP), 2019)
The future European Commission under President Ursula von der Leyen claims to be a geopolitical Commission. Sceptics note that this ambition will only further broaden the well-known gap between the capabilities of the EU and the expectations about its ability to shape foreign policy. Others welcome the fact that the 'geopolitical commission' wants to emerge from the shadow of technocratic politics. However, the postponement by EU member states in starting accession negotiations with North Macedonia in October 2019 is being viewed from this perspective as strategic blindness. The EU should not jeopardise its strategic opportunities in the neighbourhood, which will soon include the United Kingdom, by sticking to its established enlargement and neighbourhood policy. Instead, it should create new structures and invest more, both in political and material terms. One could imagine a European Political and Economic Area (EPEA) consisting of the EU and Eastern European countries of the Eastern Partnership (EaP).
Keywords: 320